PRAKTIK AGAMA TOKOH DALAM NOVEL AMONGRAGA & TEMBANGLARAS KARYA ARDIAN KRESNA (KAJIAN SOSIOLOGI SASTRA): - nurlaili rafiah, nurlaili_rafiah (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
Amongraga & Tembanglaras novel is one of the very interesting literary works to be used as research because Amongraga & Tembanglaras novel contains a lot of religious values ​​illustrated by the attitudes of the characters in it, for example, always carrying out orders by not leaving things that are required by God and religion. This study will discuss the religious activities of a Muslim who are ordered by his religion or religious practices and the purpose of this research is to explain or describe the religious activities of a Muslim who is ordered by his religion, namely by doing what God commands and avoiding everything that God forbids. The method used in this study is qualitative, the data generated in the form of descriptions in the form of words, phrases, sentences and paragraphs to find and explain in detail of an object. The results of this study indicate that in the novel Amongraga & Tembanglaras there are many religious activities of figures who always pray both the obligatory and sunnah prayers, fasting, praying, reading the Koran, and dhikr. This must be done and instilled in a Muslim from an early age so that when living in society can behave in accordance with Islamic law.